The (a -b)2formula is supplied to find the square the a binomial.This (a -b)2formula is just one of the algebraic identities. This formula is likewise known together the formula because that the square of the distinction of 2 terms. The(a -b)2formula is offered to factorize some special species of trinomials. In this formula, wefind the square of the difference of 2 terms and also thensolve it through the assist of algebraic identity. Let united state learn an ext about(a -b)2formula along with solved instances in the adhering to section.

You are watching: (a-b)^2

\"*\"

What Is(a-b)^2 Formula?

The (a -b)2formula is likewise widely well-known as the square of the difference in between the 2 terms. This formula is periodically used come factorizethe binomial. To uncover the formula of(a -b)2, us will just multiply (a -b)(a -b).

(a -b)2=(a -b)(a -b)

= a2-ab -ba + b2

= a2-2ab + b2

Therefore,(a -b)2formula is:

(a -b)2= a2-2ab + b2

Proof of(a − b)2Formula

\"*\"

Let us consider(a - b)2as the area that a square with size (a - b). In the over figure, the biggestsquare is shown with areaa2.

To prove the (a -b)2= a2-2ab + b2, take into consideration reducing the length of every sides by aspect b, and also it i do not care a - b. In the number above, (a - b)2is shown by the blue area.Now subtract the vertical and horizontal strips that have actually the area a×b. Removing a × btwice will certainly alsoremovethe overlapping square at the bottom right cornertwice hence add b2. On rearranging the data we have(a − b)2= a2− abdominal muscle − abdominal + b2. Thus this proves the algebraic identity(a − b)2= a2− 2ab + b2



Want to find facility math solutions within seconds?
Use our free online calculator come solve daunting questions. With carolannpeacock.com, uncover solutions in straightforward and simple steps.

Book a totally free Trial Class


Examples on(a-b)^2 Formula

Let usconsider few illustrations based onthe (a-b)^2 formula in this solved examples section.

Example 1:Find the worth of (x -2y)2by using(a -b)2formula.

Solution:

To find: The value of (x - 2y)2.Let united state assume the a = x and also b = 2y.We will certainly substitute these worths in (a -b)2formula:(a -b)2= a2-2ab + b2(x-2y)2= (x)2-2(x)(2y) + (2y)2= x2- 4xy + 4y2

Answer:(x -2y)2= x2- 4xy + 4y2.

Example 2:Factorize x2- 6xy + 9y2by using(a -b)2formula.

Solution:

To factorize: x2- 6xy + 9y2.We deserve to write the provided expression as:(x)2-2 (x) (3y) + (3y)2.Using(a -b)2formula:a2-2ab + b2=(a -b)2Substitute a = x and b = 3y in this formula:(x)2-2 (x) (3y) + (3y)2. = (x - 3y)2

Answer:x2- 6xy + 9y2= (x - 3y)2.

Example 3:Simplify the complying with using (a-b)2 formula.

(7x - 4y)2

Solution:

a = 7x and also b = 4yUsing formula (a - b)2 =a2 - 2ab + b2(7x)2 - 2(7x)(4y) + (4y)249x2 - 56xy + 16y2

Answer:(7x - 4y)2=49x2 - 56xy + 16y2.


FAQs top top (a -b)^2Formula

What Is the expansion of (a -b)2Formula?

(a -b)2formula is review as a minusb totality square. Its development is expressed as(a - b)2 =a2 - 2ab + b2

What Is the(a -b)2Formula in Algebra?

The (a -b)2formula is additionally known as among the importantalgebraic identities. The is review as a minusb entirety square. That is (a -b)2formula is express as(a - b)2 =a2 - 2ab + b2

How To simplify Numbers Usingthe(a -b)2Formula?

Let us know the usage of the (a -b)2formula v the help of the complying with example.Example:Find the worth of (20- 5)2using the (a -b)2formula.To find:(20- 5)2Let united state assume the a = 20 and also b = 5.We will substitute these in the formula of(a- b)2.(a - b)2 =a2 - 2ab + b2(20-5)2= 202- 2(20)(5) + 52=400-200 + 25=225Answer:(20-5)2= 225.

How To use the(a -b)2Formula give Steps?

The complying with steps are complied with while using(a -b)2formula.

See more: Kendrick Lamar Concert 2018 Concert With Schoolboy Q And Sza

Firstlyobserve the sample of the numbers even if it is thenumbers have whole ^2 as power or not.Write down the formula of(a -b)2(a - b)2 =a2 - 2ab + b2substitute the worths ofa and b in the(a -b)2formula and simplify.